Багатошарове трипільське поселення Березова, ур. Берег - Корвін-Піотровський, О.П.; Гусєв, С.О. (Археологія, 2000)
Публікація висвітлює перші результати археологічних досліджень багатошарової трипільської пам'ятки Березова, ур. Берег в Середньому Подністров'ї. Многослойное трипольское поселение Березова, ур. Берег в с. Надднестрянское Муровано-Куриловецкого р-на Винницкой обл. специально исследовалось археологической экспедицией «Днестр-3» в 1995 г. Оно занимает мысообразное возвышение левого берега водохранилища Новоднестровской ГАЭС и в настоящее время существенно размыто. На памятнике зафиксированы остатки трех слоев среднетрипольского времени: Березова, ур. Берег III, датируемый дорасписным этапом ВІ (Кукутень А1), Березова, ур. Берег II, относящийся к этапу ВІ—ВІІ (Кукутень А—В1), и Березова, ур. Берег I, соответствующий этапу ВІІ (Кукутень А—В2). Таким образом, материал многослойного поселения Березова, ур. Берег дает уникальную возможность проследить развитие трипольской культуры на среднем этапе, а в комплексе с предстоящими стратиграфическими исследованиями обеспечит существенное уточнение относительной хронологии времени от этапа ВІ до этапа ВІІ не только в среднеднестровском регионе, но и во всем трипольско-кукутенском ареале. The many-layered Trypillya settlement of Berezova the tract of Bereg near the Naddnistryans’ke village, Murovano-Kurylivtsi district, Vinnytsa region was specially studied by the archaeological expedition “Dnister-S” in 1995. It occupies a cape-like elevation of the left bank of the water reservoir of the Novodnistrovs’ka HAPP and is significantly washed out at present. On the monument, one fixed the remnants of three layers of the middle Trypillya culture: the tract of Bereg III dated as the stage BI by decorated articles (Kukuten A1); Berezova, the tract of Bereg II dated as the stage BI- ВII (Kukuten A-B1); and Berezova, the tract of Bereg 1 dated as the stage BII (Kukuten A-B2). Thus, the material of the many-layered settlement of Berezova, the tract of Bereg presents a unique possibility to trace the development of the Trypillya culture at the middle stage and will ensure, along with the forthcoming stratigraphic studies, the essential improvement of the relative chronology from the stage BI till BII not only in the middle-Dniester region but on the entire Trypillya-Kukuten area.